2020
DOI: 10.1093/ve/veaa058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the virome associated to grapevine downy mildew lesions reveals new mycovirus lineages

Abstract: The obligatory biotrophic oomycetes Plasmopara viticola is the causal agent of downy mildew, a destructive disease of grapevine worldwide. So far, chemical fungicides are widely employed to limit this pathogen, but their adverse effects are stimulating the quest for environmentally friendly alternative approaches. Here we report on the search for mycoviruses that might be later developed as biocontrol agents for this pathogen. Symptomatic leaves were collected from various regions in Spain and Italy and myceli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
175
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(186 citation statements)
references
References 99 publications
11
175
0
Order By: Relevance
“…Sclerotinia sclerotiorum ophiovirus-like virus 1 (SsOpLV1) with 7,817 nt in length shows the highest similarity to Fusarium poae negative-stranded virus 1 within the recently proposed Mycoaspiviridae family ( Chiapello et al 2020 ). SsOpLV1 contained two linearly arranged nonoverlapping ORFs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sclerotinia sclerotiorum ophiovirus-like virus 1 (SsOpLV1) with 7,817 nt in length shows the highest similarity to Fusarium poae negative-stranded virus 1 within the recently proposed Mycoaspiviridae family ( Chiapello et al 2020 ). SsOpLV1 contained two linearly arranged nonoverlapping ORFs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate that the co-infection of these unrelated viral genera is stable enough and they do not exclude each other. Indeed, multiple viral infections are known to occur in fungi and oomycetes in nature [ 16 , 17 , 20 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. However, the virus-virus interactions and the limits of accumulation of multiple viruses in a single host remain unclear [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two novel endornaviruses were found co-infecting isolates of an unidentified Phytophthora species causing asparagus rot in Japan [ 12 ]. In other oomycetes, several (+)ssRNA viruses have been described in obligate biotrophic downy mildews including Plasmopara halstedii and Plasmopara viticola [ 13 , 14 , 15 , 16 , 17 ]. Virus-like particles and/or dsRNA have been observed in Pythium irregular [ 18 ], an unclassified gammapartitivirus was reported in Pythium nuun [ 19 ], a toti-like virus was also described from two strains of Globisporangium splendens (formerly Pythium splendes ) and three virus-like sequences, Pythium polare RNA virus 1 (PpRV1), Pythium polare RNA virus 2 (PpRV2) and Pythium polare bunya-like RNA virus 1 (PpBRV1) were identified in Pythium polare infecting mosses in the Arctic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been proposed that these genera might have been evolved from Leviviridae -ancestors that infected bacterial endosymbionts, some of which may have generated mitochondria [ 39 , 45 , 75 ]. A phylogenetic reconstruction using RdRp sequences ( Figure 2 ) revealed that Lul-MV-1 is closely related to the Plasmopara viticola lesion-associated mitovirus 56 (QIR30279), a fungal mitovirus found in grapevine [ 76 ], and to a slightly lesser extent to the Wenling narna-like virus 9 (YP_009337200), identified in crustaceans [ 15 ]. The narnaviruses constituted a sister clade composed of viruses infecting either fungal or insect hosts.…”
Section: Resultsmentioning
confidence: 99%